Neck cooling improves table tennis performance amongst young national level players - Desai, T.; Bottoms, L. (Sports, 2017)
This study aimed to examine the effects of neck cooling on table tennis performance. Eight young, National level, male table tennis players (age 16 ± 2 years, height 1.77 ± 0.08 m, body mass 67.54 ± 10.66 kg) were recruited. Participants attended four testing sessions separated by a week. Session one determined fitness levels, and session two was a familiarisation trial. The final two sessions involved completing the table tennis-specific protocol either with (ICE) or without (CON) neck cooling for 1 min before each exercise period (bout: 80-90 shots), which represented an individual game. The exercise protocol required completing three bouts to represent a match, each simulating a different skill (forehand, backhand, alternate forehand and backhand), against a mechanical ball thrower. Performance was measured by the number of balls hitting two pre-determined targets. Heart rate, ratings of perceived exertion (RPE), and thermal sensation (TS) were measured. Total performance scores (shots on target) were significantly greater during ICE (136 ± 26), compared to CON (120 ± 25; p = 0.006) with a 15 (±12)% improvement. Effects for time (p < 0.05) but not condition (p > 0.05) were found for RPE and all other physiological variables. TS significantly decreased with cooling throughout the protocol (p = 0.03). Neck cooling appears to be beneficial for table tennis performance by lowering thermal sensation.